The Impact Of Digital Marketing, Electronic Word Of Mouth (E-Wom) And Personal Selling On Purchasing Decisions And The Influence Of Competitors' Products As Moderating Variables - Andy Firmansyah; Besar Agung Martono (Interdiciplinary Journal and Hummanity (INJURITY), 2023)
This study aims to explain the presence or absence of the impact of several independent variables, namely Digital Marketing, Electronic word of Mouth (e-WOM), Personal Seling and the Influence of Competitor Products as Moderating Variables on Purchasing Decisions. The purchase decision in this study is the decision to choose a copy trading application issued by PT Digital Cerberus Indonesia, a growing local cryptocurrency platform (starup). The research was conducted at a digital currency trading company, PT Digital Cerberus Indonesia, based in Bekasi, which has 2,135 users and a random research sample of 100 people was taken. PT Digital Cerberus Indonesia is a company founded by the author in 2021 and managed until now. The research instrument used is in the form of a questionnaire that has passed the validity and reliability test so that the instrument is declared valid and reliable. Furthermore, the collected data was analyzed by the SPSS 26 method including Correlation test and Multiple Regression test. The results showed that Digital Marketing variables had a positive impact on the decision to choose the Cerberus copy trading application. Word of Mouth Electronic Variables have a positive impact on the decision to choose Cerberus applications. Poersonal Selling variables have a positive impact on the decision to choose the Cerberus application. This means that the three independent variables themselves affect the decision to choose a cerberus treading coffee application. From multiple regression analysis, it is concluded that the three free variants mentioned above together (simultaneously) have a positive impact on the decision to choose the Cerberus application. The moderating variable does not have a positive impact on the decision to choose the Cerberus application.